The law relating to double jeopardy in labour law - Tshikovhi, Rotondwa Happy (University of Limpopo, 2014)
This research focuses on the application of the double jeopardy principle in labour law, section 188(1)(a (b) of the Labour Relations Act 66 of 1995, (herein the LRA) which provides that the dismissal is unfair if the employer fails to prove that the reason for the dismissal is fair and was effected in accordance with a fair procedure. The first point which I would explain is the meaning of double jeopardy and whether it is applicable in labour law. The research articulates that the double jeopardy principle applies to labour law and enumerates ways it can be applied. The South African courts, in particular, the Labour Court and the Labour Appeal Court have delivered several judgements on the double jeopardy principle. These cases will be critically discussed in detail. Comparison will be made with foreign labour law jurisprudence on the double jeopardy principle, particularly in Australia and the United States of America.
Thesis (LLM. (Labour Law)) --University of Limpopo, 2014
Keywords: Double jeopardy principle; Double jeopardy -- South Africa; Sentences (Criminal procedure) -- South Africa